Ethnic Segregation in Germany - Albrecht Glitz (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
This paper provides a comprehensive description of the nature and extent of ethnic segregation in Germany. Using matched employer-employee data for the universe of German workers over the period 1975 to 2008, I show that there is substantial ethnic segregation across both workplaces and residential locations and that the extent of segregation has been relatively stable over the last 30 years. Workplace segregation is particularly pronounced in agriculture and mining, construction, and the service sector, and among low-educated workers. Ethnic minority workers are segregated not only from native workers but also from workers of other ethnic groups, but less so if they share a common language. From a dynamic perspective, for given cohorts of workers, the results show a clear pattern of assimilation, reminiscent of typical earnings assimilation profiles, with immigrants being increasingly less likely to work in segregated workplaces with time spent in the host country.
Keywords: J61; J63; J31; 330; Ethnic Minorities; Residential Segregation; Workplace Segregation